Pruning and dormancy breaking make two sustainable grape-cropping productions in a protected environment possible without overlap in a single year - Zhipeng Qiu; Guangzheng Chen; Dongliang Qiu (PeerJ, 2019)
In table grape production, protected cultivation in a vineyard in different regions and climates is currently a commonly used practice. The aims of this study were to provide key approaches to sustainably produce two crops of grape without overlap under protected environment in a single year. Spraying the degreening chemicals 400 mg/L ethephon +0.4% sulfur at 4 weeks of vine nutrient restoration after the harvest of the summer crop resulted in the highest percentage of sprouting inflorescence. The retention of 7–10 buds in the base shoot results in the high percentage of sprouting inflorescence. Bud breaking chemicals with 2.5% hydrogen cyanamide+2.0% Baoguoliang +0.02% Shenzhonggen significantly led to sprout inflorescence more efficiently. Cluster and fruit weights of the winter crop weighed significantly less than those of the summer crop. However, the contents of total soluble sugar and titratable acidity were higher than those of the summer crop. The anthocyanin content in the peel of the winter fruit was significantly higher than that in the summer fruit. The yield of the winter crop is controlled by the yield of the summer fruit. To maintain the stability of the two crops for one year, the ratio of yield in the winter to the summer should be controlled from 2:5 to 3:5 to ensure the sustainable production of two crops without overlap for ‘Summer Black’ grape. These results may help grape growers to overcome the impacts of rainy and hot climates with the help of protected facilities, and it could enable the use of solar radiation and heat resources in subtropical and tropical areas.